SOME OPINIONS ON THE ORIGIN OF DIPLOMATIC RELATIONS BETWEEN AMIR TEMUR AND TOKHTAMISHKHAN (Scientific journal of the Fergana State University, 2023)
This article discusses some opinions about the sources of the investigation of the relationship between Amir Temur and Tokhtamysh Khan, the ruler of the Golden Horde. A comparative analysis of the identified relationships between external rights and the identification of the identified causes and the identification of the identified relationships based on the information in the source is also given.